Black Sea as a Political and Cultural Metaphor (Observations on Kristen Ghodsee’s The Red Riviera and Sylwia Siedlecka’s Golden Dusts), - Yanev, Kristiyan (Poznańskie Studia Slawistyczne, 2024)
The article analyzes the image of Black Sea littoral as a cultural and political metaphor for the processes in Bulgaria’s communist and post-communist period. Two outside critical perspectives on the recent Bulgarian history are compared – Kristen Ghodsee’s ethnographical study based on small histories of Bulgarians working in the tourism industry, whose lives were affected by the Transition period, and Sylwia Siedlecka’s collection of non-fiction texts on the physical and mental remnants of communist past, which continue to shape the present. The article outlines the image of the pre- and post-1989 period presented in the books, arguing that in both cases the sea metaphor (Red Riviera for the communist seaside project and Golden Dusts for the remains of the communist past in the post-communist present) challenge the common foreign stereotypes about Bulgaria (i.e., the Black Sea resorts, the touristic attractions).